GROOMING AND RUBBING BEHAVIOR BY MOOSE EXPERIMENTALLY INFESTED WITH WINTER TICKS (DERMACENTOR ALBIPICTUS) - Addison, Edward M.; Fraser, Douglas J.H.; McLaughlin, Robert F. (Lakehead University, 2019)
Rates of grooming, rubbing, and shaking were observed of 12 moose (Alces alces) infested with 4 levels of winter ticks (Dermacentor albipictus) and 5 uninfested control animals. Modes of grooming varied among moose and occurred with the tongue, hind feet, head, ears, antlers, teeth, and neck. Only moose with ticks used teeth and ears to groom. Uninfested moose and moose prior to being infested groomed and rubbed little. Grooming was greater immediately following than before infestation, and initial grooming and rubbing were predominant at the sites of infestation. Grooming declined in mid-winter months when nymphs develop slowly and increased in late winter and early spring when nymphs and adults actively feed; rubbing only increased in late winter and early spring. Cumulative grooming-rubbing was positively correlated with level of tick infestation and hair loss, and negatively correlated with end body weight of female calves only. Intense individual bouts of grooming and rubbing during April lasted 13–141 min. Over the entire study, cumulative grooming-rubbing in daylight hours for moose with 21,000–42,000 larvae equaled 6–28 d (μ = 12.7), and from February to April moose with 42,000 ticks groomed and rubbed on average ≥5.0–7.5 min/h. The removal of ticks was high (77–96%) indicating that grooming and rubbing are positive behavioral responses with respect to reducing the impact of winter ticks.